Recalculation of Fixed Assets in Substantive Testing of Fixed Assets by KAP BCD (Case Study at PT. XYZ) - Labila Berliana Yasmeen; Dea Arme Tiara Harahap (Rescollacom (Research Collaborations Community), 2026)
Fixed assets are a critical element of financial statements due to their material value and their direct impact on a company’s financial position and performance through depreciation. Inaccurate recognition or measurement of fixed assets may lead to material misstatements, making substantive audit procedures essential. This study aims to examine the implementation of fixed asset recalculation as part of substantive testing conducted by a public accounting firm in auditing the financial statements of PT XYZ. The research employs a qualitative descriptive approach, using observation, documentation, interviews, and literature review to obtain relevant audit evidence. The recalculation procedure focuses on verifying acquisition costs, depreciation expenses, accumulated depreciation, and book values of fixed assets in accordance with applicable accounting standards. The results show that several discrepancies were identified between management records and auditor recalculations, primarily caused by inconsistencies in depreciation timing, assets not yet in use, and misclassification of accounts. These discrepancies were subsequently corrected through audit adjustments and did not result in material misstatements in the financial statements. Overall, the study concludes that fixed asset recalculation is a vital substantive audit procedure that enhances the accuracy, reliability, and fairness of fixed asset reporting. The findings emphasize the importance of recalculation in supporting the auditor’s professional judgment and providing reasonable assurance regarding the presentation of fixed assets in financial statements.